Brice L. Erickson, Lerna, Volume VIII, The Historical Greek Village, Results of Excavations conducted by the American School of Classical Studies at Athens. - van der Enden, Mark (Journal of Greek Archaeology, 2019)
Brice Erickson’s the Historical Greek Village is an excellent new addition to the Lerna series and significantly furthers our understanding of the nature and character of the site from circa 970 to 175 BC. Volume VIII in the series follows contributions that detail the fauna, people and prehistoric pottery and architecture of Lerna. Ericson’s Historical Village not only presents an important and rich corpus of material, it also attempts to interpret the available archaeological data to reconstruct the nature and character of the site and its place within the wider Argolid. In this the books succeeds marvellously and Ericson’s work significantly furthers our understanding of village life and culture in Geometric – Hellenistic times.